2019
DOI: 10.3390/vibration2010005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Seismocardiography

Abstract: Cardiovascular disease is a major cause of death worldwide. New diagnostic tools are needed to provide early detection and intervention to reduce mortality and increase both the duration and quality of life for patients with heart disease. Seismocardiography (SCG) is a technique for noninvasive evaluation of cardiac activity. However, the complexity of SCG signals introduced challenges in SCG studies. Renewed interest in investigating the utility of SCG accelerated in recent years and benefited from new advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 115 publications
(256 reference statements)
0
157
0
Order By: Relevance
“…For the latter, it has been shown that the morphology of the vibrational cardiac waveforms varies with the respiratory volume [39,40], and methods of extracting respiratory phases [41,42], effort [43] and breathing states such as normal, breathless, long, and labored [44] have been proposed. However, the interindividual morphological variations, as well as dependencies on numerous parameters including subject position, are still challenging [45]. SCG and PCG are closely related [46], with differences mostly defined by their frequency ranges [47].…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…For the latter, it has been shown that the morphology of the vibrational cardiac waveforms varies with the respiratory volume [39,40], and methods of extracting respiratory phases [41,42], effort [43] and breathing states such as normal, breathless, long, and labored [44] have been proposed. However, the interindividual morphological variations, as well as dependencies on numerous parameters including subject position, are still challenging [45]. SCG and PCG are closely related [46], with differences mostly defined by their frequency ranges [47].…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…All the parameters are defined in Equations (1)-(4) where ( ) d n is the desired signal. Sensors 2020, 20, x 3 of 14 ( ) ( ) ( ) n d n y n    (4) The adaptive control unit updates the coefficients using the input vector and the prior estimation error. The detailed information can be described in Equation (5): (5) where ( ) n k is the gain vector that is described in Equation (6): (6) where  is the forgetting factor and ( ) n P is a covariance matrix of the noise which can be updated by Equation (7):…”
Section: Theory Of Adaptive Recursive Least Squares Filter (Arlsf)mentioning
confidence: 99%
“…With the development of an accelerometer with high-sensitivity, low-noise, small-size, high-efficiency, and high-robustness signal-processing technology, SCG has shown its great potential to be used by wearables. Consequently, it is now feasible to use the information in clinical applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 In addition, micro-vibrations of the chest wall in the low frequency range of DC-100 Hz are linked to mechanical cardiac events and contain information about valve functionalities and cardiac muscle contractility. 22,23 Moreover, changes in the lung volume during the respiratory cycle cause macro-motions of the thorax and abdomen with ultralow frequency below 1 Hz. 24 This signal is useful to extract the respiratory pattern, which is significant in predicting clinical deterioration of patients with chronic airflow obstruction, 25,26 and diagnose several other respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%